Óleo de quiabo como fonte alternativa para produção de biodiesel e avaliação de antioxidantes naturais em biodiesel etílico de soja - Calixto, Clediana Dantas (2011)
Biodiesel has been implemented in a commercial scale in Brazil 2005 and is currently being use like additive in the diesel in proportion to 5%, firmly is consolidating in the Brazilian energy matrix. However, its use is still facing serious problems to beovercome. One of the aspects involves the question of raw material used for the production of biofuel, because despite the country being a barn of oilseeds, soybeans still constitutes the main source producer. Another obstacle is the high susceptibility to oxidation of certain types of biodiesel, which requires the use of antioxidant additives to increase the lifetime of them. In this work we evaluate the technical qualities of biodiesel fuel produced from oil, okra, non conventional oilseed, biodiesel and blends of soybean and okra on the proportions of 25 and 50% (v / v). The results showed a profile of fatty acid esters of biodiesel of okra, with a high composition of unsaturated esters (65.42%) mainly of ethyl linoleate, but with a significant amount of palmitate (30.44%). The flow properties of biodiesel showed values concordant with the norms established by the ANP for sale. The oxidative to performed according with EN 14112 showed an induction period of 7.54 h, meeting the specification 6h.In relation to the blends, the 50% plus the induction period of biodiesel from soybean 3.11h to 5.80h. In contrast to blend of 25% had pro-oxidant effect of soybean biodiesel. In the present study we investigated also the antioxidant efficacy of natural extracts lemon peels, and the pomegranate and herb stems and leaves of the camellia sinensis, (green tea) in the correction of oxidative stability to of biodiesel fromsoy beans. Where it was found that all extracts showed antioxidant effect, bringing periods of induction of ethyl of soybean biodiesel in the three experiments made accelerated oxidation, PetroOxy, Rancimat and PDSC. The ethanol extract of green tea at a concentration of 2000 mg kg-1 appeared as the most effective among the rest, getting fit the induction period of biodiesel from soybeans to the specified minimum value.